Otomatisasi Pencatatan dan Kepatuhan Regulasi Terhadap Keberlanjutan UMKM Pengendalian Internal Sebagai Moderasi - Imanuel, Rizky; Risal, Risal; Afif, Ali (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Given their large number and contribution to the country's GDP, micro, small, and medium enterprises (MSMEs) play a significant role in the Indonesian economy. However, corporate sustainability presents challenges for business actors, particularly related to the implementation of internal controls, automation of recording, and regulatory compliance. This study uses a quantitative approach by utilizing primary data as a data source. This study uses a purposive sampling method to select MSME respondents. The data analysis process uses SPSS version 26. Data analysis is carried out through descriptive statistics, data quality tests for validity and reliability, classical assumption tests, multiple linear regression, and moderated regression analysis (MRA) with the help of SPSS version 26. Data were collected through questionnaires, and 89 returned questionnaires were declared eligible and represent all research respondents. From the analysis results, simultaneously recording automation, regulatory compliance is proven to have an effect on the sustainability of MSMEs, internal control is not proven to moderate the relationship between the two variables, partially recording automation is proven to affect the sustainability of MSMEs shown by a value of 0.016 <0.05, and regulatory compliance is proven to affect the sustainability of MSMEs shown by a value of 0.02 <0.05, while internal control does not moderate the relationship between recording automation with a value of 0.721>0.05, regulatory compliance 0.731>0.05. The implications of these findings indicate the importance of awareness of business actors in implementing effective internal control in running their businesses.